Neotypification of Terminalia paniculata (Combretaceae) - Chakrabarty, Tapas; Kumar, Venkatachalam Sampath (Phytotaxa, 2017)
While preparing a revised treatment of the family Combretaceae for “Flora of India Project,” our attention was drawn on Terminalia paniculata Roth (1821: 383) which was described on the basis of a specimen collected by Benjamin Heyne from peninsular India. The species is well documented in Indian Floras (e.g. Wight & Arnott 1834, Beddome 1869, Brandis 1874, Clarke 1878, Cooke 1903, Talbot 1911, Gamble 1919 and Chandrabose 1983). Gangopadhyay & Chakrabarty (1997) in their revision of the family Combretaceae of Indian subcontinent mentioned that the type of this species is not extant. The type material of T. paniculata housed in the Berlin herbarium (B; herbaria acronyms follow Thiers 2017) was presumably destroyed during the World War II. In the Kew herbarium (K), there is a collection by Benjamin Heyne (K000786096: image!) identified and listed in Wallich’s Numerical List as T. triopteris B.Heyne ex Wallich (1831: no. 3980B). This material contains two twigs, one flowering and the other fruiting and this appears to be a specimen not seen by Roth (1821) since he clearly mentioned in the protologue: “Fructum non vidi.” Thus, as per the provisions of the Code (Mc Neill et al., 2012), as there is no other extant original material (Article 9.7) traceable, a neotype (Articles 9.11 and 9.13) is designated here for T. paniculata from Peninsular India, where Benjamin Heyne made botanical explorations (Burkill, 1965). The neotype specimen is housed in the Central National Herbarium, Botanical Survey of India, Howrah, India (CAL) and its duplicate in the Madras Herbarium, Botanical Survey of India, Southern Regional Centre, Coimbatore, India (MH).